Morpho-agronomic analysis of three roselle (Hibiscus sabdariffa L.) mutants in tropical Malaysia - Osman, Mohamad; Golam, Faruq; Saberi, Shabnam; Abdul Majid, Nazia; Nagoor, Noor Hasima (Southern Cross Journals, 2011)
Conventional hybridization in roselle (Hibiscus sabdariffa L.) is difficult due to its cleistogamous nature of reproduction. To overcome this limitation, an intensive mutation breeding program using different doses of gamma radiation was conducted. In total, five generation of three mutants were developed from the variety ‘Arab’. A number of Morpho-agronomic and physico-chemical characteristics including plant height, canopy diameter, number of branches per plant, number of fruits per branch, number of fruits per plant, weight of fruits per plant, weight of fresh calyx per plant, weight of dry calyx per plant, weight of capsule per plant of these mutants of roselle (Hibiscus sabdariffa L.), designated UKMR-1, UKMR-2 and UKMR-3, were evaluated in tropical environment of Malaysia. Significant differences were observed in morpho-agronomic characters in these three mutants. UKMR-2 showed better performance for weight of fruits per plant (2170.7 g) and weight of fresh calyx per plant (1408.4 g); whereas for number of fruits per branch, number of fruits per plant and weight of capsule per plant UKMR-3 showed better performance. The life cycle of mutants was shorter and their lodging resistant was significantly higher compared to their parents and local check.